Ways to Open Science. Open Research Infrastructures and the role of repositories - Blumesberger, Susanne (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. The Way to Open Science contains many components. One of these components would be open repositories based on open source software with free access to researchers. Open access policies are essential, as are open infrastructures and open contents. Repositories can support this openness by offering open licenses, open metadata , the possibility to use open formats and open thesauri. Another principal point is transparency. Open peer review should be possible, and the description of processes should also be transparent. Of course, an open license should provide all data types and metadata as well. It is important to help researchers to make their results visible and accessible and to encourage them to publish in OA-Journals and use repositories for the underlying data. Open Access Policies are supporting these efforts. Open data can be freely used, modified, and shared by anyone for any purpose. In order to do so, Open Licenses are required. Also Metadata are important components of the Way to Open Science. Metadata are data about data which should be free of all restrictions on access, structured and based on standards. Open formats are defined by a published specification and are not restricted in their use. They are mainly used by open-source software. Open Thesauruses are freely accessible for everyone without costs and with a free license. Open Processes should be documented, transparent, repeatable and reusable. An open peer review process is also a step forward to Open Science. Authors and referees are no longer anonymous. The whole process and the decision letters are open. Of course Open licenses allow the reuse of any work or data without any restrictions. The lecture will deal with various aspects of open science and focus on the role of repositories – with all chances and challenges.